Enhancing detection of Listeria monocytogenes in food products using an enzyme. (March 2023) - Felton, Samantha; Armstrong, Cheryl; Chen, Chin-Yi; He, Yiping; Lee, Joe; Reed, Sue; Akula, Nikki; Walker, Sharon; Berger, Bryan W.; Capobianco, Joseph
Abstract: There is a need to identify the presence of microorganisms, in particular human pathogens, in food processing facilities and products. Adhesion of pathogens to surfaces poses a detection challenge with biofilms greatly hindering detection by precluding the transfer of specific material to downstream sensors. Enzymes that disrupt biofilms can therefore enhance detection of foodborne pathogens through facilitating their release from abiotic and biotic surfaces. In this study, a recombinant enzyme, CAase, was applied to improve detection of biofilm-embedded Listeria monocytogenes on food and food contact surfaces. Microbiological and molecular detection methods demonstrated that biofilms treated with enzyme for longer than 4 h resulted in a significant increase in the number of cells released into the media compared to untreated controls. This work demonstrates the benefits of inclusion of enzymes and biosurfactants within sample processing and detection protocols because of their ability to contribute to a more rapid, accurate, reliable, and repeatable microbial detection assay when biofilm embedded pathogens are present. Highlights: Sample preparation for detecting microbial pathogen in foods. Enzymatic treatment of biofilms to facilitate microbial pathogen detection. Method to detect microbial pathogens in foods and on food contact surfaces.